The Impact Of Peer To Peer Lending And Payment Gateways On Msme Performance Is Moderated By Product Innovation - Ayu Dannisa Sarah Mudmainah; Kustiadi Basuki (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to examine the effect of peer to peer lending and payment gateways on MSME performance moderated by product innovation. The population in this study were SMEs in the Tanjung Priok sub-district with a total sample of 150 and sampling using purposive sampling. Data analysis uses Smart-PLS 4 which has the result that peer to peer lending has a positive and significant effect on MSME performance. Payment gateway has a positive and significant effect on MSME performance. Product innovation has a positive and significant effect on the performance of SMEs. Innovation moderation has a positive and significant effect that strengthens the influence of peer to peer lending on MSME performance. Innovation moderation has a significant positive effect and strengthens the influence of payment gateways on MSME performance.